Factors that Influence the Income of Rice Farmers in Mappesangka Village, Ponre District, Bone Regency - Resa Padilla; Andi Jam'an; Warda Warda (Pustaka Digital Indonesia, 2026)
This research is important to identify the factors influencing rice farmers’ income at the village level, providing a basis for effective agricultural policies, improving farmers’ welfare, and strengthening regional food security. This research is a type of quantitative research with the aim of finding out the factors that influence the income of rice farmers in Mappesangka village, Ponre subdistrict, Bone district. This sample was taken from Mappesangka village, Ponre subdistrict, Bone district. The type of data used in this research is quantitative data obtained from distributed questionnaires and is related to the problem being studied. Data collection was carried out by observation and distribution of questionnaires. In this research, the data sources used for data collection include primary data and secondary data. The main findings of this study show that land area and labor wages are the dominant factors affecting rice farmers’ income, while production costs do not have a significant influence. Based on the results of data research using statistical calculations through the Statistical Package for the Social Science (SPSS) version 29 application regarding the influence of land area, production costs, and labor wages on the income of rice farmers in Mappesangka village, Ponre subdistrict, Bone district which was discussed previously, the author draws the conclusion that the land area variable has a positive and significant effect on income, the production cost variable has a positive and insignificant effect on income, and the labor wage variable has a negative and significant effect on income. The use of labor is reduced by switching to technology so that the wages for the labor used can decrease.